Growth of Epitaxial Oxide Thin Films on Graphene - Petrov,PK; Zou,B; Walker,C; Wang,K; Tileli,V; Shaforost,O; Harrison,N; Klein,N; Alford,N (Scientific Reports, 2016)
The transfer process of graphene onto the surface of oxide substrates is well known.However, for many devices, we require high quality oxide thin films on the surface ofgraphene. This step is not understood. It is not clear why the oxide should adopt theepitaxy of the underlying oxide layer when it is deposited on graphene where there isno lattice match. To date there has been no explanation or suggestion of mechanismswhich clarify this step. Here we show a mechanism, supported by first principlessimulation and structural characterisation results, for the growth of oxide thin films ongraphene. We describe the growth of epitaxial SrTiO3 (STO) thin films on a grapheneand show that local defects in the graphene layer (e.g. grain boundaries) act as bridgepillarspots that enable the epitaxial growth of STO thin films on the surface of thegraphene layer. This study, and in particular the suggestion of a mechanism forepitaxial growth of oxides on graphene, offers new directions to exploit thedevelopment of oxide/graphene multilayer structures and devices.